2017
DOI: 10.1038/ncomms14668
|View full text |Cite
|
Sign up to set email alerts
|

Bioaerosol generation by raindrops on soil

Abstract: Aerosolized microorganisms may play an important role in climate change, disease transmission, water and soil contaminants, and geographic migration of microbes. While it is known that bioaerosols are generated when bubbles break on the surface of water containing microbes, it is largely unclear how viable soil-based microbes are transferred to the atmosphere. Here we report a previously unknown mechanism by which rain disperses soil bacteria into the air. Bubbles, tens of micrometres in size, formed inside th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
151
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(155 citation statements)
references
References 55 publications
2
151
0
2
Order By: Relevance
“…We don't know the degree to which these organisms influence cloud formation or precipitation but the relationships likely operate in both directions. Many particles are washed out of the air by rain, though the impact of droplets on surfaces can also yield increases (Joung et al 2017). Indeed these combined effects are known to modify the composition of airborne bacteria, for example observations in Korea indicate that after rainfall the airborne abundance of some families such as Carnobacteriaceae and Clostridiales typically decreased while the non-spore forming Actinobacteria such as the Propionibacteriaceae increased (Jang et al 2017).…”
Section: Ice Formationmentioning
confidence: 99%
“…We don't know the degree to which these organisms influence cloud formation or precipitation but the relationships likely operate in both directions. Many particles are washed out of the air by rain, though the impact of droplets on surfaces can also yield increases (Joung et al 2017). Indeed these combined effects are known to modify the composition of airborne bacteria, for example observations in Korea indicate that after rainfall the airborne abundance of some families such as Carnobacteriaceae and Clostridiales typically decreased while the non-spore forming Actinobacteria such as the Propionibacteriaceae increased (Jang et al 2017).…”
Section: Ice Formationmentioning
confidence: 99%
“…Organisms have been isolated from as high as 77 km (Imshenetsky et al, 1978). Many studies have investigated composition, abundance and variability of PBAs across a variety of ecosystems (Bowers et al, 2011;Cuthbertson et al, 2017;Griffin et al, 2010;Harding et al, 2011;Joung et al, 2017;Pearce et al, 2010). Many studies have investigated composition, abundance and variability of PBAs across a variety of ecosystems (Bowers et al, 2011;Cuthbertson et al, 2017;Griffin et al, 2010;Harding et al, 2011;Joung et al, 2017;Pearce et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers showed that when a rain droplet hits soil, 0.01% of the bacteria on the soil surface are emitted into air as a bioaerosol. 107 Legionella has been shown to persist in soil, 108-110 and it is possible that the bacteria could be aerosolized either through rainfall or wind-induced suspension. Although some of the bacteria in the soil may come from industrial waste or cooling towers, Rowbotham 111 suggested that amoebae in soil might enhance the growth of Legionella .…”
Section: Introductionmentioning
confidence: 99%